Changes in behavior as side effects in methylphenidate treatment: review of the literature - Konrad-Bindl DS; Gresser U; Richartz BM (Neuropsychiatric Disease and Treatment, 2016)
Doris Susanne Konrad-Bindl,1 Ursula Gresser,1 Barbara Maria Richartz2 1Department of Internal Medicine, University of Munich, Munich, 2Clinic der Jägerwinkel, Bad Wiessee, Germany Background: Our review of the scientific literature focused on an analysis of studies describing instances of methylphenidate treatment leading (or not) to behavioral changes in the pediatric, adolescent, and adult populations.Materials and methods: We conducted a literature search in PubMed, Medline, and Google using the keywords “methylphenidate”, “behavioral changes”, “adverse effects”, and “side effects”. A total of 44 studies were identified as reporting on the effects and adverse effects of methylphenidate administration, and were included in the analysis.Results: Five studies specifically set out to study, record, and discuss changes in behavior. Eight studies did not set out to study behavioral effects, but record and discuss them. A total of 28 studies recorded behavioral effects, but failed to discuss these further. Three studies did not include behavioral effects.Conclusion: This review records what data have been published in respect of changes in behavior in association with the use of methylphenidate. While there is some evidence to suggest that methylphenidate causes changes in behavior, the majority of the studies reviewed paid little or no attention to this issue. Based on the available data, it is impossible to determine the point at which such behavioral effects occur. The frequency of occurrence of behavioral effects is also impossible to determine with certainty. Based on the available data, it is not possible to rule out whether behavioral effects may persist or not persist once treatment is discontinued. In conclusion, despite countless publications and extensive administration, especially to children, we have insufficient data to judge the long-term effects and risks of methylphenidate taking. Keywords: methylphenidate, changes in behavior, attention-deficit/hyperactivity disorder, children, adults, adverse effects